2020
DOI: 10.1080/22221751.2020.1806735
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring SARS-CoV-2 gene deletions close to the spike S1/S2 cleavage site in the viral quasispecies of COVID19 patients

Abstract: The SARS-CoV-2 spike (S) protein, the viral mediator for binding and entry into the host cell, has sparked great interest as a target for vaccine development and treatments with neutralizing antibodies. Initial data suggest that the virus has low mutation rates, but its large genome could facilitate recombination, insertions, and deletions, as has been described in other coronaviruses. Here, we deep-sequenced the complete SARS-CoV-2 S gene from 18 patients (10 with mild and 8 with severe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
(30 reference statements)
2
60
1
Order By: Relevance
“…Even if several studies report variants found at frequencies below 0.1 (25,27,37-39) only a few evaluated the confidence of such calls (26,40). We found that the number of variants with VAF>0.1 detected in samples with at least 1000 g.c.p.r is similar between contemporaneous samples and increases with time since the start of the outbreak, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Even if several studies report variants found at frequencies below 0.1 (25,27,37-39) only a few evaluated the confidence of such calls (26,40). We found that the number of variants with VAF>0.1 detected in samples with at least 1000 g.c.p.r is similar between contemporaneous samples and increases with time since the start of the outbreak, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing technical replicates of multiple cDNAs generated from the same sample has been proposed as a mitigation strategy to identify iSNVs more reliably [ 23 ]. However, whereas amplicon-based sequencing has been widely used for the analysis of low-frequency variants [ [20] , [21] , [22] , 37 , 38 ] only a few studies thus far have evaluated the confidence of such calls and have implemented the sequencing of cDNA replicates to ensure accuracy [ 23 ]. False positives have also been reported among high-frequency variants supported by good sequencing depth, indicating that the risks of inaccurate sequencing are not limited to suboptimal samples [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACE2-binding affinity of the S protein is one of the most important determinants of SARS-CoV-2 infectivity and disease severity. While some of the S protein mutations enhance ACE2 binding, resulting in increased susceptibility and severity of COVID-19, others can inhibit S protein binding or result in a truncated S1 protein, conferring a high degree of resistance to infection or reducing the severity of it [ [116] , [117] , [118] ].
Fig.
…”
Section: Coronaviruses and Ace2mentioning
confidence: 99%